Predictors of Children’s Early Numeracy: Environmental Variables, Intergenerational Pathways, and Children’s Cognitive, Linguistic, and Non-symbolic Number Skills - Bernabini, Luca; Tobia, Valentina; Guarini, Annalisa; Bonifacci, Paola (Frontiers in Psychology, 2020)
Early numeracy skills in preschool years have been found to be related to a variety of different factors, including Approximate Number System (ANS) skills, children's cognitive and linguistic skills, and environmental variables such as home numeracy activities. The present study aimed to analyze the differential role of environmental variables, intergenerational patterns, children’s cognitive and linguistic skills, and their ANS in supporting early math skills. The sample included 64 children in their last year of kindergarten and one parent of each child. Children were administered a battery of cognitive and linguistic tasks, and a nonsymbolic comparison task as a measure of ANS. Parents were administered similar tasks assessing cognitive skills, math skills, and ANS skills (estimation and nonsymbolic comparison), together with a questionnaire on home numeracy. Results showed that home numeracy predicted children's early math skills better than a number of parent and child variables. Considering children's skills, their ability in the nonsymbolic magnitude comparison task was the strongest predictor of early math skills. Results reinforce the importance of the role of home numeracy activities and children’s ANS skills above that of parents’ math skills.